ASSOCIATE NURSING STUDENTS’ PERCEPTIONS TOWARD NURSING PROFESSION IN JORDAN - Al Jarrah, Ibrahim Ali Tawfiq (European Scientific Journal, ESJ, 2013)
﻿The image of both nurses and nursing as a profession are vital in the successful recruitment and retention of staff in the health care industry (Annelie Meiring, 2010). This study design to overview the image of nursing among associate nursing students in south Jordan. The study was conducted on Balqa Applied University, Jordan, Karak and Aqaba college branches, Faculty of Nursing for student enrolled in associate nursing program. Three main parts were selected, profession view, dependent and independent order of work and personal growth. The data collected through self-administered questionnaire containing three major parts: The first part is the sociodemographic characteristics; the second part is image of nursing; the third part is social rank of job. The study involved a randomly selected 100 students from both sites,68 questionnaires were analyzed by (SPSS)15. Descriptive Statistics were done using numbers, percentage, arithmetic mean ,standered deviation and one sample test. The study showed that the associate nursing students generally have a significance positive perceptions about the image of the nursing profession. The highest percentage of study subjects joined the faculty of nursing because of financial reasons/ availability of work. Majority of the students feel proud when talking with others about nursing profession. The relationship with medical members and the family member opinion have the greatest effect in changing the image of nursing profession. This study concluded that a majority of the respondents preferred teaching institution and bedside nursing after the graduation.